Vertical gardens for green beauty - Janakiram, T.; Sonkhle, Usha; Jain, Ritu; Namita, Namita (Indian Horticulture, 2019)
In the age of shrinking land and rapid multiplication of high rises, the space available for gardens is becoming limited. The concepts of innovative and environment-friendly vertical garden can be a solution for increasing concrete mass in urban areas and shrinking horizontal spaces. The combination of aesthetics with environmental principles through vertical gardens or green walls will certainly change the conventional urban gardening.